Ostatnie pożegnanie w starożytnej Grecji. Przebieg ceremoniału pogrzebowego według satyry Lukiana z Samosat O opłakiwaniu umarłych - Wilczak, Wiktoria (Colloquia Litteraria, 2024)
In ancient Greece, funeral ceremony was closely linked to the belief in life aſter death and was of great importance to the deceased and his loved ones. Religion, law and social conditions influenced funeral arrangements that eliminated the threat of contagion and were crucial to inheritance rights. Legal regulations included the number of participants in the ceremony and public displays of grief to temper emotions. In his satire, Lucian of Samosata mockingly described the details of Greek funeral ceremonies, while highlighting their problems and links to ancient Greek culture and tradition.